2021
DOI: 10.1038/s41598-021-87089-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute partial-body cryostimulation on cognitive performance, cerebral oxygenation, and cardiac autonomic activity

Abstract: We assessed the effects of a 3-min partial-body cryostimulation (PBC) exposure—where the whole body is exposed to extreme cold, except the head—on cognitive inhibition performance and the possible implications of parasympathetic cardiac control and cerebral oxygenation. In a randomized controlled counterbalanced cross-over design, eighteen healthy young adults (nine males and nine females) completed a cognitive Stroop task before and after one single session of PBC (3-min exposure at − 150 °C cold air) and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
(34 reference statements)
0
5
1
Order By: Relevance
“…Interestingly, both in our, and previous studies, cryotherapy improved selected cognitive abilities, while others were unaffected. For example, Theurot et al [31] showed an improvement in the reaction time but not accuracy on the Stroop test, while we showed an improvement in the processing speed, cognitive flexibility and executive control but not in DSST set shifting. A meta-analysis by Pilcher et al [36] showed importance of parameters such as the duration of exposure to the experimental temperature, or the duration of the task, for the effect on cognitive performance [36].…”
Section: Influence Of Wbc On Cognitive Functioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Interestingly, both in our, and previous studies, cryotherapy improved selected cognitive abilities, while others were unaffected. For example, Theurot et al [31] showed an improvement in the reaction time but not accuracy on the Stroop test, while we showed an improvement in the processing speed, cognitive flexibility and executive control but not in DSST set shifting. A meta-analysis by Pilcher et al [36] showed importance of parameters such as the duration of exposure to the experimental temperature, or the duration of the task, for the effect on cognitive performance [36].…”
Section: Influence Of Wbc On Cognitive Functioncontrasting
confidence: 62%
“…Within these limitations however, ours and previous studies consistently show a beneficial impact of cryotherapy on cognitive function. Specifically, a recent investigation, using WBC in an older population with mild cognitive impairment, showed an improvement in immediate recall on Dem-Tect test and orientation on Test Your Memory task [28], while three studies in healthy populations, albeit using partial extreme cold application to the head [29], cheeks [30], and the body apart from the head [31], showed improvement in executive function, namely in cognitive inhibition measured by the Stroop task [28][29][30][31].…”
Section: Influence Of Wbc On Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no definitive findings about cryotherapy's effects on muscle regeneration [8,9]. Cryo-compression is aimed at lowering the temperature of the tissues [10,11] and reducing inflammation in the damaged area [12][13][14]. Studies have shown that CC reduces swelling [11,14] and improves tissue perfusion [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…HRV tests do not require expensive apparatuses, besides reliable monitors capable of beat-by-beat acquisition. Current literature reports that WBC involves the autonomic drive at rest (Louis et al 2015(Louis et al , 2020Theurot et al 2021), but these studies did not address the effect of exercise. Instead, Sautillet et al (2021) tested the WBC effect by applying it only after exercise, thus leading to a cumulative evaluation of both factors.…”
Section: Introductionmentioning
confidence: 99%